At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
we can replace tanx with y this making the equation
3y^2 - 5y - 2 = 0 so we solve for y
Δ = b^2 - 4ac (a=3 b=-5 c=-2)
Δ = 25 + 24 = 49
y1 = (5 + 7) / 6 = 12/6 = 2
y2 = (5 - 7) / 6 = -2/6 = -1/3
since tan is positive in the first and third quadrant and according to the question x belongs somewhere in the first two quadrants the following is true
for y1 = tanx = 2 only applies for the first quadrant ( from 0° to 90°) while for y2 = tanx = -1/3 it can only apply for the second quadrant (from 90° to 180°). i hope this made sense because english is not my first language.
3y^2 - 5y - 2 = 0 so we solve for y
Δ = b^2 - 4ac (a=3 b=-5 c=-2)
Δ = 25 + 24 = 49
y1 = (5 + 7) / 6 = 12/6 = 2
y2 = (5 - 7) / 6 = -2/6 = -1/3
since tan is positive in the first and third quadrant and according to the question x belongs somewhere in the first two quadrants the following is true
for y1 = tanx = 2 only applies for the first quadrant ( from 0° to 90°) while for y2 = tanx = -1/3 it can only apply for the second quadrant (from 90° to 180°). i hope this made sense because english is not my first language.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.